An improved time‐domain analytical method for LLC resonant converters and dead time designs for zero‐voltage switching - Jian Jiao; Xizheng Guo; Chenchen Wang; Xiaojie You; Kai Li (IET Power Electronics, 2023)
Abstract In this paper, an improved time‐domain analytical method for LLC resonant converters is proposed. Unlike traditional time‐domain analytical methods, the resonant current in the dead time is derived by considering the equivalent capacitances of the switching devices and the transformer. The equivalent output capacitance of the primary‐side switch is calculated by using a two‐segment fitting approach. The equivalent capacitance of the transformer is calculated by using the six‐capacitor model. The current increment method is used to calculate the initial value of the magnetizing current and to determine the numerical calculation conditions for the proposed time‐domain expressions. Finally, the dead time ranges for zero‐voltage switching of the converter are derived based on the improved time‐domain method. Experiments were carried out with a 10 kW LLC resonant converter. The lower limit of the dead time calculated with the proposed method is closer to the experimental results than the values of two conventional methods.